Conceptualising environmental governance in turbulent times: Insights from Brexit and waste in the UK. (August 2020) - Cowell, Richard; Flynn, Andrew; Hacking, Nick
Abstract: Institutional turbulence created by the UK's EU exit (Brexit) prompts a wider need to re-think whether our conceptualisations of governance in the environmental sphere sufficiently understand the dynamics of change. In this context, Boltanski and Thévenot's 'Orders of Worth' (OoW) framework, has particular merit. This conceptualises governance regimes as composed of compromises between plural and incommensurable orders of the public good, with innate potential for instability; especially - we would add - when the territoriality of governance is in flux. The OoW approach is applied to an analysis of waste governance debates in the UK following the 2016 EU referendum. Documentary and interview data show how present and prospective governance arrangements in the waste and resources sector are subject to rival justifications, with actors advancing different compromises between economic, industrial, civic and environmental orders, but that each is also attached to conceptions of the relevant governance scale (EU, UK, devolved nation). Our study shows the wider potential fragility of environmental reforms, arising from the secondary status of environmental concerns in compromises with dominant market, industrial and civic orders. The 'orders of worth' framework requires attention to the scales of political authority being mobilised in disputes, which add their own incommensurability. Highlights: Environmental governance is especially vulnerable to policy turbulence. The orders of worth framework explains the instability of environmental governance. Environment is a secondary concern in governance compromises, making it vulnerable. Actors conceptualise circular economies in different ways, materially and spatially. The research shows the need for a spatial dimension to the orders of worth framework.